Bacillus lipopeptides inhibit lipase activity and promote 3T3-L1 preadipocyte differentiation - Meichun Chen; Deju Chen; Rongfeng Xiao; Xuefang Zheng; Bo Liu; Jieping Wang (Taylor & Francis Group, 2024)
Bacillus lipopeptides have been reported to display anti-obesity effects. In the present study, Lipopeptides from Bacillus velezensis FJAT-45028 that consisted of iturin, fengycin and surfactin were reported. The lipopeptides exhibited a strong lipase inhibition activity in a concentration-dependent manner with a half maximal inhibitory concentration of 0.012 mg/mL, and the inhibition mechanism and type were reversible and competitive, respectively. Results of CCK8 assay showed that 3T3-L1 preadipocyte cells were completely viable under treatment of 0.050-0.2 mg/mL lipopeptides for 24 or 48 h. It was found that the lipopeptides could increase lipid droplets in the differentiated 3T3-L1 adipocytes in tested concentration and suppress the expression of peroxisome proliferator-activated receptor gamma (PPARγ). These results indicated the potential anti-obesity mechanism of the tested lipopeptides might be to inhibit lipase activity but not to suppress lipid accumulation in the adipocytes. Moreover, the lipopeptides could elevate glucose utilisation by 14.43%-33.81% in the differentiated 3T3-L1 adipocytes.